Aesthetic and symbolic aspects versus usability: Evaluation of daily use product - lemon squeezer - Lanutti, Jamille Noretza de Lima [UNESP]; Campos, Lívia Flávia de Albuquerque [UNESP]; Pereira, Douglas Daniel [UNESP]; de Mattos, Liara Mucio [UNESP]; Inokuti, Elen Sayuri [UNESP]; Paschoarelli, Luis Carlos [UNESP] (My University, 2012)
Usability has been characterized as a requirement in the development of product design. Besides the physical aspects, the subjects’ perception and their relationship with objects of daily use have been the focus of research in usability. In this sense, the rejection of a product by the user is not necessarily related to being complex or inefficient, but may be associated with factors and aesthetic significance. The objective of this study was to do a perceptual evaluation with objects of daily use, seeking to identify the relationship between product usage factors and factors related to the aesthetic and symbolic values that can be assigned to it. The procedures were based on ethical recommendations. Twelve subjects participated (average age 20,62, s.d. 1,66), that evaluated six different models of lemon manual through Semantic Differential Test composed of ten descriptors related to subjective aspects of the product (modern/classic, beautiful/ugly, common/unusual, essential/dispensable, elegant/inelegant, repulsive/attractive, funny/serious, known/unknown, rational/emotional, humble/sophisticated). The results were analyzed statistically using the nonparametric Wilcoxon test. This analysis demonstrated higher sensitivity (p≤ 0,05) to the descriptors related to subjective aspects of the product (51,33% of cases) when compared to the descriptors of product use (20,66% of cases). However, significant differences (p ≤ 0.05) with these product use descriptors indicate that the shape and morphological structure of the products influence their perceived usability. As an example, two presses with completely opposite morphological characteristics showed significant results (p ≤ 0,05) opposites in all analyzed using descriptors. Thus, the results demonstrate that the Semantic Differential Test for descriptors related to the use of the product allows a significant perceptual assessment and other tests may contribute to the usability of product/system.
Keywords: Ergonomic design; Juicers; Perception; Semantic differential; Usability